103 Atypical Progressive Bulbar Palsy presenting with Dropped Head (2020)
Introduction: Typical amyotrophic lateral sclerosis (ALS) presents on neurological examination with specific signs of upper and lower motor neuron degeneration (Brooks et al, 1995), which can account for 85% of patients with ALS (Turner and Talbot, 2013). There are different types of clinical presentations, including progressive bulbar palsy (PBP), Limb-onset ALS, progressive muscular atrophy (PMA) and upper motor neuron (UMN) predominant ALS. PBP has mainly brainstem signs. There are a few case reports of dropped head syndrome in ALS, mainly in patients with the limb involvement variant. Methods: Case report Results: A 56 year old right-handed male, presented to the clinic with four months of dysphagia to liquids and solids, neck pain and progressive neck weakness causing constant drop head. No dysarthria or other neurological symptoms, no dyspnea. Neurological examination: Cranial Nerve (CN) CN XII: Nasal voice, bilateral atrophy of the tongue with tremor and fasciculations. Motor: Diffuse atrophy and decreased tone of the sternocleidomastoid and trapezii bilaterally, strength: 2/5 in neck flexors and extensors. Sensory: Hypoesthesia of the tongue. The rest of his neurological examination was normal. Labs: Routine blood work, thyroid function tests, collagen vascular work-up, and protein electrophoresis were normal. Creatine Phosphokinase (CPK) and Acetylcholine Receptor Antibodies (AChR Ab) were negative. Brain and Spinal Cord MRI: Showed mild brainstem, cerebellar and cervical spinal atrophy. Conclusions: Patients with ALS initially present with symptoms localized to the limbs or bulbar muscles. A very small percentage 1-2% of ALS patients had neck muscle weakness with head drop (Jokelainen et al, 1977; Gourie-Devi et al, 2003). However, in all the previously reported cases, the patients had limb involvement at the time of presentation which was absent in this case, and the head drop occurred after the onset of symptoms (Lange et al, 1986; Katz et al; 1996). Dropped head syndrome can be seen in inflammatory myopathies, myasthenia gravis, facioscapulohumeral muscular dystrophy, spinal muscular atrophy, nemaline myopathy and carnitine deficiency (Umapathy et al, 2003) but ALS should also be considered in patients with atypical presentations.